A constitutive model of concrete based on Ottosen yield criterion. (1st June 2020) - Zhang, Xueyan; Wu, Haijun; Li, Jinzhu; Pi, Aiguo; Huang, Fenglei
Abstract: The development of a constitutive model of concrete materials under multiaxial forces is an important problem in engineering science, and such a model is the theoretical basis for studying various mechanical behaviors. Based on the Ottosen yield criterion, a cap model parameter is proposed in this paper to describe the yielding behavior of concrete under high hydrostatic pressure; in addition, hardening and softening parameters are considered to reflect the hardening and softening of concrete during the stress state change, thus completely representing the yielding behavior according to the Ottosen criterion. A nonassociative flow rule for the Ottosen yield criterion is established to accurately calculate the strain change of concrete specimens and describe the expansion of concrete. The calculation is performed based on the established constitutive model, and the calculated results are compared with the results of uniaxial, biaxial, triaxial compression and uniaxial tension experiments on normal- and high-strength concrete. The comparison results show that the calculated stress–strain curves are in agreement with the experimental data. Hence, the proposed model can explain the stress–strain relationship and strength characteristics of concrete at different strengths.